Iron oxide and gold bimetallic radiosensitizers for synchronous tumor chemoradiation therapy in 4T1 breast cancer murine model. Issue 22 (24th May 2021) - Nosrati, Hamed; Baghdadchi, Yasamin; Abbasi, Reza; Barsbay, Murat; Ghaffarlou, Mohammadreza; Abhari, Fatemeh; Mohammadi, Ali; Kavetskyy, Taras; Bochani, Shayesteh; Rezaeejam, Hamed; Davaran, Soodabeh; Danafar, Hossein
Abstract : The development of highly integrated multifunctional nanomaterials with a superadditive therapeutic effect and good safety is an urgent but challenging task in cancer therapy research. Abstract : The development of highly integrated multifunctional nanomaterials with a superadditive therapeutic effect and good safety is an urgent but challenging task in cancer therapy research. The present study aims to design a nanoplatform that offers the opportunity to enhance antitumor activity while minimizing side effects. Given the Au-mediated X-ray radiation enhancement and the ability of Fe-based nanomaterials to create reactive oxygen species (ROS) and DNA damage, we anticipated that bimetallic Fe3 O4 –Au heterodimer would bring strong radiosensitizing capacity. Fe3 O4 –Au heterodimer surface was covered with bovine serum albumin (BSA) to achieve good surface functionality, stability and prolonged blood circulation. Folic acid (FA) moieties were added to the nanoformulation to increase tumor-homing, specificity and uptake. Finally, curcumin (CUR) was incorporated into the nanoparticle to function as a natural anticancer agent. The integration of all these components has yielded a single nanoplatform, Fe3 O4 –Au–BSA–FA–CUR, capable of successfully fulfilling the mission of superadditive cancer therapy to avoid the risks of organ removal surgery. The efficacy of the proposed nanoplatform was investigated in vitro and in vivo . High radiosensitizing ability, X-ray-induced ROS generation and DNA damage, and good biocompatibility were demonstrated through in vitro experiments. Also, the administration of Fe3 O4 –Au–BSA–FA–CUR with X-ray irradiation completely eradicated the tumor without any mortality and toxicity in healthy tissues in vivo . Our results highlight the potential of CUR-loaded Fe3 O4 –Au–BSA–FA heteronanostructure to enable synergistic localized radiochemotherapy and open up a new door to attractive possibilities that warrant further exploration.